Admissibility analysis and stabilization for neutral descriptor hybrid systems with time-varying delays. (August 2019) - Zhuang, Guangming; Xia, Jianwei; Feng, Jun-e; Zhang, Baoyong; Lu, Junwei; Wang, Zhen
Abstract: This paper focuses on admissibility analysis and stabilization for neutral descriptor hybrid systems (NDHSs) with time-varying delays. The main object is to design mode dependent state feedback controller (SFC) and realize admissibility and stabilization of the NDHSs. Sufficient conditions are provided in terms of linear matrix inequalities (LMIs) via constructing integrated L-K functional. Two simulation examples including a partial element equivalent circuit (PEEC) model are used to testify the validity and practicality of the proposed method.